IMPLEMENTATION OF THE METHOD OF KINEMATIC DECOMPOSITION FOR CALCULATIONS IN NONLINEAR FORMULATION - E. K. Agakhanov; G. M. Kravchenko; L. N. Panasyuk; E. V. Trufanova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Method kinematic decomposition in a physically non-linear formulation of solid mechanics computations of the screw piles AKSIS taking into account soil models based on the hypothesis marginal surface of the Mises - Schleicher - Botkin.